Impact of Treatment Parameters on Racial Survival Differences in Oropharyngeal Cancer: National Cancer Database Study. (June 2022) - Zhu, Daniel; Wong, Amanda; Oh, Eun Jeong; Ahn, Seungjun; Wotman, Michael; Sahai, Tanmay; Bottalico, Danielle; Frank, Douglas; Tham, Tristan
Objective: To investigate how differences in treatment parameters account for survival differences between races of patients with oropharyngeal squamous cell carcinoma (OPSCC). Study Design: Retrospective cohort study. Setting: National Cancer Database. Methods: Data of patients with OPSCC undergoing radiation therapy (RT) or concurrent chemoradiation therapy as primary treatment were obtained from the National Cancer Database from 2004 to 2016. We analyzed 4 treatment-related time intervals to determine their impact on survival between races when controlling for human papilloma virus (HPV) status. Cox proportional hazards models, stepwise logistic regressions, covariate adjustments, and propensity score matching were performed. Results: A total of 3152 patients were identified (2877 White, 275 Black). In HPV– cases, Black patients with prolonged radiation duration had a significantly worse overall survival as compared with White patients (hazard ratio, 1.77; 95% CI, 1.03-3.05; P = .039). In a logistic regression model, the only covariate that was significantly associated with prolonged RT was facility type. When further adjusted for facility type, the survival difference between Black and White patients with HPV– status and prolonged RT times was no longer significant (hazard ratio, 1.55; 95% CI, 0.90-2.69; P = .116). Conclusions: There is a significant disparity in overall survival between Black and White patients with HPV– OPSCC when RT duration is prolonged. Clinicians should be aware of the negative impact of prolonged RT, especially in Black patients, so that they can attempt to decrease treatment-related time intervals. Facility type was also found to affect the outcomes of patients with OPSCC, and efforts should be made to improve patient access to well-equipped, high-volume facilities.